2007
DOI: 10.1158/1078-0432.ccr-07-0284
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I Biodistribution and Pharmacokinetic Trial of Humanized Monoclonal Antibody Hu3s193 in Patients with Advanced Epithelial Cancers that Express the Lewis-Y Antigen

Abstract: ). The first infusion of hu3S193 was trace labeled with Indium-111, and biodistribution, pharmacokinetics, tumor uptake, and immune response were evaluated in all patients. Results: A total of 15 patients (7 male/8 female; age range, 42-76 years; 6 breast, 8 colorectal cancer, and 1non^small-cell lung cancer) were entered into the study. Transient grade 1to 2 nausea and vomiting was observed following infusion of hu3S193 at the 40mg/m 2 dose level only. There was one episode of dose-limiting toxicity with self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
1
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 26 publications
0
50
1
2
Order By: Relevance
“…The chimeric gene was composed of extracellular singlechain anti-Le Y , [46][47][48] linked to the hinge region of CD8 followed by the transmembrane and cytoplasmic domains of CD28 and the cytoplasmic portion of CD3-z. 49 The gene was incorporated into the Moloney murine leukemia virus-based plasmid, pSAMEN.…”
Section: Retroviral Vector Productionmentioning
confidence: 99%
“…The chimeric gene was composed of extracellular singlechain anti-Le Y , [46][47][48] linked to the hinge region of CD8 followed by the transmembrane and cytoplasmic domains of CD28 and the cytoplasmic portion of CD3-z. 49 The gene was incorporated into the Moloney murine leukemia virus-based plasmid, pSAMEN.…”
Section: Retroviral Vector Productionmentioning
confidence: 99%
“…The safety of this approach is supported by the favorable toxicity profile of various 'naked' and conjugated anti-Le Y antibodies in early phase clinical studies, as well as the lack of transforming events in T cells retrovirally transduced to express this construct. [37][38][39][40] An alternative to the use of chimeric T cells for the treatment of Le Y expressing malignancies is the less cumbersome utilization of monoclonal antibodies. [38][39][40] However, chimeric T cells as used in this study effectively combine antigen specificity with direct activation of the most potent immune effector cells upon antigen binding.…”
Section: Discussionmentioning
confidence: 99%
“…[37][38][39][40] An alternative to the use of chimeric T cells for the treatment of Le Y expressing malignancies is the less cumbersome utilization of monoclonal antibodies. [38][39][40] However, chimeric T cells as used in this study effectively combine antigen specificity with direct activation of the most potent immune effector cells upon antigen binding. Therefore, in our opinion, chimeric T cells are more likely to mount …”
Section: Discussionmentioning
confidence: 99%
“…Conjugation of calicheamicin to hu3s193 antibody directed against Lewis y antigen (CD174), which is overexpressed on gastric carcinomas [78] as well as carcinomas of the colon, breast, lung, prostate, and ovary, demonstrated antitumor activity in vivo and caused growth arrest of xenografted gastric carcinomas for at least 100 days [79]. The first clinical trials of humanized antibody hu3s193 in patients with advanced epithelial cancer confirmed high selectivity in tumor targeting and favorable pharmacokinetics [80]. Targeting tumor cells positive for putative CSC-related markers with ADCs has the potential to eliminate CSCs as well as tumor cells without stem-like properties positive for a designated antigen.…”
Section: Cancer Stem Cell-targeted Therapiesmentioning
confidence: 99%